Dopant effect on structural and optical properties of undoped and silver-doped zinc oxide (SZO) thin films prepared by sol-gel method - Nur Rasyidah, Rusli (2016)
Transparent of pure and silver doped ZnO thin films were successfully fabricated by simple sol-gel method and spin coating technique. The effect on structural and optical properties between pure and silver doped ZnO thin films have been characterized by Attenuated Total Reflectance (ATR-FTIR), X-ray Diffractometer (XRD), ultravioletvisible (UV-Vis) spectrophotometer and Field Emission Scanning Electron Microscopy (FESEM). ATR analysis was used to identify the functional groups occur in the samples. While XRD analysis result show that all of the sample of pure and silver doped ZnO thin film has the highest peak at (101) direction that have hexagonal wurtzite structure. The crystallite size of all are in range of 0.2480 Å and 0.3216 Å. The optical properties was analyzed by UV-Vis spectrophotometer. The results showed that the exciton absorption of ZnO and silver doped ZnO (SZO) occur between 358 nm ad 362 nm. The transmittance spectra showed that ZnO have high transmittance (above 90 %) and for SZO between 78% and 89 %. The grain size and surface morphology of ZnO and SZO thin films samples decrease with increasing the silver dopant.